Green Marketing and Consumer Behavior: An Analytical Literature Review and Marketing Implications - Chea, Ashford C. (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The article’s purpose has been to conduct a comprehensive and critical review of the empirical literature on green marketing and consumer behavior to determine emerging issues and trends. It begins with an outline of the relevant theoretical framework that underpins green marketing and consumer behavior. Next, the paper presents a rigorous analysis of the current scientific literature. This is followed by an assessment of emerging trends and issues derived from the literature review. Lastly, the article draws relevant marketing implications and outlines appropriate recommendations for managerial decision-making.